A tethered tolane: twisting the excited state - Kozhemyakin, Yury; Krämer, Maximilian; Rominger, Frank; Dreuw, Andreas; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
The synthesis of a doubly bridged tolane is reported. The target is obtained in a five-step synthesis, starting from commercially available 2-amino-meta-xylene by a combination of a Sandmeyer reaction, radical bromination, and Stille-type coupling, followed by double ring closing. The doubly tethered tolane is crystalline; the two phenyl rings are highly twisted with respect to each other both in solution and in the solid state. Optical spectroscopy and quantum chemical calculations show that the doubly bridged tolane is twisted not only in the ground state, but also in the excited state, leading to emission from the twisted state in solution and in the solid state. Strong phosphorescence is observed at cryogenic temperatures.
Version of record online: September 11, 2018
Gesehen am 30.01.2020